Mandibular incisor inclination and gingival recession after treatment with the Jasper Jumper: a 10-year follow-up - Wilana Moura; José Fernanado C. Henriques; Caroline M. Gambardela-Tkacz; Paula Cotrin; Daniela Garib; Guilherme Janson (SpringerOpen, 2021)
Abstract Objective To evaluate the long-term outcomes of Class II treatment with the Jasper Jumper appliance and comprehensive orthodontic treatment concerning inclination of the mandibular incisors and gingival recession. Methods Sixteen patients with Class II malocclusion at a mean age of 12.54y (SD = 1.17) were treated with the Jasper Jumper appliance and comprehensive orthodontic treatment. The mean treatment time was 2.05y (SD = 0.21). Dental records were taken before (T1), after treatment (T2) and 11.90y (SD = 0.48) after debonding (T3). The frequency of gingival recession, clinical crown height and mandibular incisor position were evaluated using intraoral photographs, digital models and lateral cephalograms. Interphase changes were evaluated using dependent t and McNemar's tests. Correlation between clinical crown height and final position of the mandibular incisors was evaluated using Pearson correlation test (P < 0.05). Results The frequency of gingival recessions increased over time and was observed in 6 (9.4%), 12 (18.8%) and 24 (37.5%) of the mandibular incisors at T1, T2 and T3, respectively. A significant increase in labial inclination and protrusion of the mandibular incisors was observed between T1 and T2 interval. The clinical crown height significantly increased in the follow-up period (T3-T2) and in the complete observation time (T3-T1). There was no correlation between the amount of labial inclination and protrusion of the mandibular incisors and clinical crown height for all time intervals. Conclusion No significant correlation between the amount of labial movement of the mandibular incisor and clinical crown height increase was found.